P2X7 is expressed on human innate‐like T lymphocytes and mediates susceptibility to ATP‐induced cell death. Issue 11 (19th October 2022) - Winzer, Riekje; Serracant‐Prat, Arnau; Brock, Valerie J.; Pinto‐Espinoza, Carolina; Rissiek, Björn; Amadi, Miriam; Eich, Niklas; Rissiek, Anne; Schneider, Enja; Magnus, Tim; Guse, Andreas H.; Diercks, Björn‐Philipp; et al.
Abstract: Extracellular ATP activates the P2X7 receptor, leading to inflammasome activation and release of pro‐inflammatory cytokines in monocytes. However, a detailed analysis of P2X7 receptor expression and function in the human T cell compartment has not been reported. Here, we used a P2X7‐specific nanobody to assess cell membrane expression and function of P2X7 on peripheral T lymphocyte subsets. The results show that innate‐like T cells, which effectively react to innate stimuli by secreting high amounts of pro‐inflammatory cytokines, have the highest expression of P2X7 in the human T cell compartment. Using Tγδ cells as example for an innate‐like lymphocyte population, we demonstrate that these cells are more sensitive to P2X7 receptor activation than conventional T cells, affecting fundamental cellular mechanisms like calcium signaling and ATP‐induced cell death. The increased susceptibility of innate‐like T cells to P2X7‐mediated cell death provides a mechanism to control their homeostasis under inflammatory conditions. Understanding the expression and function of P2X7 on human immune cells is essential to assume the benefits and consequences of newly developed P2X7‐based therapeutic approaches. Abstract : Innate‐like T cells are ready‐to‐go effectors and have the highest expression of the ATP receptor P2X7 in the human T cell compartment. P2X7 expression renders these cells susceptible to ATP‐mediated cell death, which may constitute a mechanism for controlling immune pathology in an ATP‐rich, inflammatory environment.